TREATMENT OF SINUSITIS WITH THE YAMIK SINUS CATHETER - Furukido, Kyosuke (JIBI INKOKA TEMBO, 2003)
The YAMIK sinus catheter (YAMIK) has recently been reported to be a useful therapeutic device for the treatment of sinusitis. The present study was conducted to investigate the therapeutic effects of YAMIK and compare its delivery of normal saline (NS) and betamethasone solution (0.4mg/ml) into the paranasal sinuses. The following parameters were evaluated : (i) clinical nasal symptoms (nasal discharge, nasal obstruction, postnasal drip, and headache); (ii) radiographs (ethmoid and maxillary sinuses); and (iii) cytokine levels (IL-1 β, IL-8, and TNF- α) determined by enzyme-linked immunosorbent assay. Nasal symptoms, i.e., nasal discharge, nasal obstruction, postnasal drip, and headache, in 45.5%, 78.9%, 56.5%, and 76.5%, respectively, of the patients. The radiographic findings in the ethmoid and maxillary sinuses improved in 51.7% and 87.5%, respectively, of the patients. Levels of the cytokine IL-1β, IL-8, and TNF- α correlated with the total X-ray scores (Rs = 0.396, Rs = 0.402, and Rs = 0.319, respectively). The total nasal symptom scores decreased significantly after the first therapy and the total X-ray scores significantly decreased after therapy with NS or the betamethasone solution. The levels of IL-1 β and IL-8 in both the NS and betamethasone groups, had significantly decreased at the third and second week, respectively, whereas the TNF- α level decreased after the first treatment with betamethasone solution and remained unchanged after treatment with NS. These findings suggest that YAMIK is clinically effective in the treatment of sinusitis, and that evacuation of pathological effusions in the sinuses may exert a beneficial effect by reducing the levels of IL-1 β and IL-8. We speculate that removal of pathological effusions from the sinuses may exert its therapectic effect through different mechanisms than the mechamisms of the effect of betamethasone.